Precision nutrition management in hyperlipidemia-associated acute pancreatitis: mechanistic insights and personalized therapeutic approaches - Ma, Jingyuan; Wan, Xing; Liu, Jifeng; Hu, Xuyang; Ma, Yanna; Gao, Yunhai (Frontiers in Nutrition, 2025)
Hyperlipidemia-associated acute pancreatitis (HLAP), an acute inflammatory disorder triggered by dyslipidemia, has witnessed a rising global incidence with significant health implications. The pathogenesis of HLAP involves complex interactions among lipid metabolism dysregulation, inflammatory cascades, and oxidative stress. Conventional therapeutic approaches, while providing partial symptomatic relief, exhibit limitations in addressing individual variability. Precision nutrition management emerges as a novel paradigm integrating multi-omics profiling (genomic, metabolomic) and clinical parameters to develop personalized intervention strategies. This comprehensive review analyzes the pathophysiological mechanisms linking lipid dyshomeostasis to HLAP progression, systematically evaluates the scientific foundation for precision nutrition interventions, and identifies key gaps in current implementation strategies. Furthermore, we examine current research limitations and outline future avenues for enhancing therapeutic efficacy via personalized nutritional interventions.